Pengembangan Media Pembelajaran Interaktif “Guru 3D” pada Mata Pelajaran Animasi 3 Dimensi - Afifuddin Afifuddin; Budi Santosa; Tri Kuat; Fitri Nur Mahmudah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to analyze, develop, and test the effectiveness of interactive learning media in 3D Animation subjects. This research uses research and development methods using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at SMK Muhammadiyah 1 Sleman Yogyakarta. The subjects in this study were class XI students of Multimedia SMK Muhammadiyah 1 Sleman. This research design uses data collection techniques using questionnaires to analyze product needs, using validity tests to test the feasibility of the developed products and using Quasy experiment pretest-posttest to test effectiveness. This research uses validators of design experts, material experts, linguists and media experts to validate interactive learning media to be developed. The validity results that have been given by experts in the product validity test show an average percentage of 96% which shows very good and valid qualification. Analysis of research data was carried out by using the validity of questionnaires and T-tests to compare achievement results in classes before being applied to experimental and control classes. The significant difference is evidenced by the results of the T-test calculation which explains that equal variances assumed sig values. (2-tailled) of 0.012 < 0.05, so the data shows significant. These results show the effectiveness of the